Study on the mechanism of mulberry polyphenols inhibiting oxidation of beef myofibrillar protein. (15th March 2022) - Huang, Xiang; Sun, Lu; Liu, Lan; Wang, Guoze; Luo, Peng; Tang, Daobang; Huang, Qun
Highlights: Mulberry polyphenols promote the unfolding and aggregation of myofibrillar protein structure. Mulberry polyphenols facilitate the transformation from α-helix to β-turn structure of myofibrillar protein. Mulberry polyphenols help ameliorate the degradation of myofibrillar protein gel properties due to oxidation. Protein aggregation caused by excessive addition of polyphenols deteriorates the gel properties of proteins. Abstract: In order to explore the mechanism of mulberry polyphenols inhibiting the oxidation of myofibrillar protein (MP), the effect of mulberry polyphenols on the structure and physicochemical properties of MP in the oxidation system was investigated. The results revealed that the content of carbonyl group and sulfhydryl group of MP was notably reduced, while the Zeta potential, storage modulus G' and surface hydrophobicity were improved when the addition of mulberry polyphenol was 0.5%. SDS-PAGE showed an irreducible aggregation of mulberry polyphenols with proteins. Fluorescence spectroscopy and FT-IR analysis manifested that mulberry polyphenols promoted the unfolding of protein structure and the transformation of α-helix to β-turn structure. Scanning electron microscopy (SEM) observed that oxidation with polyphenols facilitated the cross-linking and aggregation of MP more tightly. Nevertheless, excessive addition (≥1.0%) weakened its gel properties. Thus, to maintain the good quality of meat products, both polyphenols addition and oxidation intensity should be controlled simultaneously.